Intravenous Chlorpromazine for the Short-Term Treatment of Insomnia in End-Stage Cancer Patients With Difficulty in Oral Administration. (3rd July 2018) - Hasuo, Hideaki; Fujii, Ryohei; Uchitani, Kazuki; Sakuma, Hiroko; Kanbara, Kenji; Fukunaga, Mikihiko
Abstract: The objective of the study was to evaluate effectiveness and safety of intravenous chlorpromazine for the short-term treatment of insomnia in end-stage cancer patients. Insomnia occurs as one of distressing symptoms in 70% of end-stage cancer patients. End-stage cancer patients often have difficulty in oral administration because of disease progress. We retrospectively evaluated 30 end-stage cancer patients with difficulty in oral administration who received intravenous chlorpromazine for the short-term treatment of insomnia. A primary end point was sleep quality based on St. Mary's Hospital Sleep Questionnaire 3 days after the treatment. Improved sleep quality was observed on the day after the treatment and later ( P < .001), and the effective rate mean was 0.63 (95% confidential interval: 0.45–0.81) 3 days after the treatment. Increased total sleep time and decreased sleep latency time were observed 3 days after the treatment ( P < .001); however, no improvement in depth of sleep was achieved ( P = .231). There was no adverse event except for two delirium cases. The study indicated that intravenous chlorpromazine can be applied safely and effectively for the short-term treatment of insomnia in end-stage cancer patients with difficulty in oral administration.